Enabling Managed Retreat from Coastal Hazard Areas through Property Acquisition and Transferable Development Rights: Insights from Western Australia. Issue 3 (2nd July 2020) - Robb, Ashley; Stocker, Laura; Payne, Michele; Middle, Garry John
ABSTRACT: This article presents an examination of (1) key factors that are likely to influence the establishment and implementation of property acquisition and transferable development rights (TDR) programmes, for the purposes of enabling managed retreat from coastal hazard areas; and (2), local government attitudes to and perceptions of the potential extent to which these factors are likely to influence the successful implementation of such programmes. This research identifies various challenges that will need to be overcome if these programmes are to be successfully implemented by local government to enable managed retreat and potential solutions for resolving these challenges.